Comparison of the histopathological characteristics of osteomyelitis, medication-related osteonecrosis of the jaw, and osteoradionecrosis. Issue 1 (January 2019) - Shuster, A.; Reiser, V.; Trejo, L.; Ianculovici, C.; Kleinman, S.; Kaplan, I.
Abstract: The purpose of this study was to compare the histopathological parameters of chronic/suppurative osteomyelitis, medication-related osteonecrosis of the jaw (MRONJ), and osteoradionecrosis (ORN), and to examine the hypothesis that distinct histological features can be related to a specific disease, allowing for diagnosis based on microscopic evaluation alone. One hundred and ten samples were reviewed by two examiners in a blinded fashion, and a semi-quantitative histomorphometric analysis was performed. The parameters evaluated included the presence or absence of necrotic bone, inflammation, reactive bone formation, bacteria, and osteoclasts. No statistically significant differences were found between groups for any parameter. Necrotic bone was common to all three diagnoses. Inflammation and reactive bone formation were present in all three diagnoses. The presence of bacteria was a prominent feature in all cases. Osteoclasts were scarce in MRONJ and osteomyelitis, and non-existent in ORN. The results of this study failed to identify distinctive microscopic characteristics in any of the three entities that could be used to differentiate between them. Therefore, it is impossible to reach a specific final diagnosis based on microscopic findings alone. The role of microscopic analysis is to serve as an aid to diagnosis that must be complemented by the patient's history and imaging.